2020
DOI: 10.1111/padr.12311
|View full text |Cite
|
Sign up to set email alerts
|

Living Alone over the Life Course: Cross‐National Variations on an Emerging Issue

Abstract: The increasing proportion of persons living alone has come to be emblematic in many ways of modern Western societies because it represents the importance conceded to the individual and to individual goals at the expense, basically, of the family. Solo living has been interpreted within the context of changing values and preferences, changing personal and conjugal realities, and the changing work contexts so often associated with the Second Demographic Transition. We know little about patterns and trends in liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 38 publications
6
51
0
5
Order By: Relevance
“…Our study’s findings with regard to living situation are in line with previously reported general population trends [ 16 , 33 , 34 ]. The result that males more often live alone may partly be due to higher financial independence of males, and traditional gender/family roles of women in many societies, whereby women stay with kin if they are single and only leave the family when they themselves have found a family [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study’s findings with regard to living situation are in line with previously reported general population trends [ 16 , 33 , 34 ]. The result that males more often live alone may partly be due to higher financial independence of males, and traditional gender/family roles of women in many societies, whereby women stay with kin if they are single and only leave the family when they themselves have found a family [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study’s findings with regard to living situation are in line with previously reported general population trends [ 16 , 33 , 34 ]. The result that males more often live alone may partly be due to higher financial independence of males, and traditional gender/family roles of women in many societies, whereby women stay with kin if they are single and only leave the family when they themselves have found a family [ 33 ]. The finding that older people and people with less severe injuries more often reported to live alone may be related to the higher self-sufficiency and better access to financial resources that enable independent living in a single household, which is also reflected in the finding that those with higher income more often live alone.…”
Section: Discussionsupporting
confidence: 93%
“…Living alone is also associated with depression in older adults (76). The current pandemic potentially adds to the already high percentages of older adults living alone (77). For some older adults with depression, the pandemic-related bereavement might also affect their remission (78).…”
Section: Bereavement and Loneliness: Lasting Effects Of The Covid-19 mentioning
confidence: 99%
“…As a result of all of these factors, at present percentages of living alone have reached extremely high levels, as high as 50% or more among women (aged 75-79) and 20-30% among men. Levels are by far the highest in the most developed nations of the world, but there is some indication that they are on the rise everywhere (Esteve et al, 2020). Recent research has also shown a sharp growth in the proportion living alone in later life although, in some countries where it peaked relatively early (Nordic countries, the UK, the USA), there has been a moderate decline in these rates over the past 20 years, though not in the actual number of elderly living alone (Reher and Requena, 2019).…”
Section: The Societal Contexts Of the Pandemicmentioning
confidence: 99%